The mediating impact of sustainability on the relationship between agility and operational performance - Raed El Khalil; Mohamad Ali Mezher (Operations Research Perspectives, 2020)
Agility and sustainability are two philosophies that the North American manufacturing industry invested heavily in, since the beginning of the twenty-first century. The impact of the two philosophies go beyond operations and extend to innovation, employees, communities, and customer. This paper identified the lack of empirical research investigating the relationship between agility and sustainability as well as their combined interactions with operational performance metrics. Very few researchers investigated this relationship with limited depth and breadth. Therefore, this paper investigated the interaction between sustainability, agility, and their influence/impact on operational performance in the United States (US) automotive manufacturing Industry. Based on the literature review conducted and after consulting several particulars from the US automotive manufacturing industry a survey was developed, this survey reflects a comprehensive list of agility practices, sustainability practices, and top-five performance metrics utilized by the US automotive industry. A survey was carried out with a total of 212 respondents. Respondents are all top managers at 152 manufacturing facilities including assembly/manufacturing, Powertrain, and component plants. We established a comprehensive list that includes seven agility categories with 52 factors and identified the top five performance metrics. The results identify a significant and positive relationship between agility and sustainability, agility and operational performance, and sustainability and operational performance. The result shows a significant correlation between agility practices and sustainability. An agility performance index was determined by combining the analytic hierarchy process and partial least square. Utilizing the partial least square method, sustainability was identified as a mediator on the relationship between Agility and operational performance.
Keywords: 330; Agility; Manufacturing industry; Operations performance metrics; Sustainability